المسار التحولي للشعرية من الأنموذج البلاغي الأرسطي إلى الأنموذج البنيوي - بن شيحة, نصيرة (جامعة الوادي - University of Eloued, 2020)
ملخص: تسعى هذه المقالة إلى تعقب المسار التحولي الذي شهدته الشعرية بدءا من ظهورها، المرتبط بالأنموذج البلاغي الأرسطي، الذي يعد بمثابة السند التأسيسي لمبحث الشعرية، بوصفها مجالا بحثيا يهدف إلى وضع القواعد والمعايير التي تحدد الملامح الفنية والجمالية للأجناس الأدبية التي تنهض على عنصر التمثيل والمحاكاة. إلا أن هذا المفهوم التأسيسي الذي اكتسبته الشعرية مع أرسطو، قد تعرض لانعطافات متعددة دفعت إلى تغيير مساره التحليلي، فكان أن تأثر ت جل المباحث الأدبية -بما فيها الشعرية- بطبيعة التحول الفني والأدبي الذي أفرزته المرحلة الرومانسية، الذي أحال وقائع تحليل النص الأدبي إلى مقاربة نفسية واجتماعية لا تمت بصلة للبنية الداخلية للعمل الأدبي، وهو ما أدى إلى ضرورة انفتاح الدراسات الأدبية على الإجرائية العلمية التي تكرست في الأنموذج اللساني البنيوي. Abstract: This article attempts to track the transformative path that poetry has walked down since its emergence. An emergence that was linked to the Aristotelian rhetorical paradigm and represented the founding basis for the poetic research, as a field of research that aimed at setting rules and standards to define the technical and aesthetic features of the literary genres. These literary genres hence relied on the element of representation and simulation. However, this foundational concept that poetics acquired with Aristotle, has been subjected to multiple turns that led to changing its analytical path. Therefore, the literary fields of study - including poetics – were influenced by the nature of the artistic and literary transformation produced by the romantic phase. This same transformation led, also, the analysis of the literary text to adapt an unrelated psychological and social approach to the internal structure of literary work. As consequences, it became a necessity for literary studies to open up to the scientific procedure that was enshrined in the structural linguistic model.
مقال
Keywords: الشعرية ; الجمالية ; البلاغة ; الأجناس الأدبية ; البنيوية ; الخطاب; poetics ; aesthetic ; rhetoric ; literary genres ; structuralism ; discourse